Quorum sensing inhibiting activity of Streptomyces coelicoflavus isolated from soil - Hassan eRamadan; Mona I. Shaaban; Fatma eAbdel Bar; Areej eEl-Mahdy; Shadi eShokralla; Shadi eShokralla (Frontiers in Microbiology, 2016)
Quorum sensing (QS) systems communicate bacterial population and stimulate microbial pathogenesis through signaling molecules. Inhibition of QS signals potentially suppresses microbial infections. Antimicrobial properties of Streptomyces have been extensively studied, however, less is known about quorum sensing inhibitory (QSI) activities of Streptomyces. This study explored the QSI potential of Streptomyces isolated from soil. Sixty-five bacterial isolates were purified from soil samples with morphological characteristics of Streptomyces. The three isolates: S6, S12, and S17, exhibited QSI effect by screening with the reporter, Chromobacterium violaceum. Isolate S17 was identified as Streptomyces coelicoflavus by sequencing of the hypervariable regions (V1-V6) of 16S rRNA and was assigned gene bank number KJ855087. The QSI effect of the cell-free supernatant of isolate S17 was not abolished by proteinase K indicating the non-enzymatic activity of QSI components of S17. Three major compounds were isolated and identified, using spectroscopic techniques (1D, 2D NMR and Mass spectrometry), as behenic acid (docosanoic acid), borrelidin and 1H-pyrrole-2-carboxylic acid. 1H-pyrrole-2-carboxylic acid inhibited QS and related virulence factors of Pseudomonas aeruginosa PAO1 including; elastase, protease and pyocyanin without affecting Pseudomonas viability. At the molecular level, 1H-pyrrole-2-carboxylic acid suppressed the expression of QS genes (lasI, lasR, lasA, lasB, rhlI, rhlR, pqsA and pqsR). Moreover, QSI activity of S17 was assessed under different growth conditions and ISP2 medium supplemented with glucose 0.4% w/v and adjusted at pH 7, showed the highest QSI action. In conclusion, 1H-pyrrole-2-carboxylic acid, one of the major metabolites of Streptomyces isolate S17, inhibited QS and virulence determinants of P. aeruginosa PAO1. The findings of the study open the scope to exploit the in vivo efficacy of this active molecule as anti-pathogenic and anti-virulence of P. aeruginosa.